The time traveler's wife [videorecording (DVD)] - Schwentke, Robert, 1968-; McAdams, Rachel, 1978-; Bana, Eric; Howard, Arliss; Livingston, Ron; Niffenegger, Audrey (New Line Home Entertainment : Distributed by Warner Home Video, 2010)
Clare has been in love with Henry her entire life. She believes they are destined to be together, even though she never knows when they will be separated: Henry is a time traveler, cursed with a rare genetic anomaly that causes him to live his life on a shifting timeline, skipping back and forth through his lifespan with no control. Despite the fact that Henry's travels force them apart with no warning, Clare desperately tries to build a life with her one true love.